A agenda legislativa da indústria (CNI): a ação política dos industriais no Congresso [1996-2021] - Silva, Haroldo da (2023)
The main argument in this thesis is that the uncritical adoption of the principles of the neoliberal agenda by Brazilian industrialists, represented by the CNI, transformed into agendas, through the Industry Legislative Agenda, defended in the Brazilian Congress between 1996 and 2021, with a view to reducing the "Brazil Cost", were, largely, counterproductive for the sector's objectives. To support this assertion, a wide-ranging analysis of the literature on the political action of interest groups was carried out, including an investigation into the reasons that led to Brazil's early deindustrialisation process and correlating it with the choices made by industrialists in the field of legislative proposals. In order to achieve this, in addition to the bibliography, historical data from the entire period of the formulation of the Legislative Agenda for the Industry sector was analysed, with different sections and, most importantly, 23 in-depth empirical interviews were conducted (between 2021 and 2023) with important players from the industrial field involved in the sector, with different views from the ideological field, but with a privileged and pragmatic perspective on the sector's competitiveness problems. The main focus was on trying to answer why the success of the demands made to Congress was not reflected in a higher level of systemic competitiveness in the industry. The conclusion reached is that the unrestricted adoption of neoliberal premises, carried out by the political action of industrialists, quite competently by the CNI, decisively contributed to reducing the density of industry in the Brazilian economic and social fabric